ANALISIS PENGELOLAAN KEUANGAN DESA DENGAN PENDEKATAN PERATURAN MENTERI DALAM NEGERI REPUBLIK INDONESIA NOMOR 113 TAHUN 2014 DI DESA ULUWAE : indonesia - Desi Rahmiyanti; Yustina Nofiane Bhubhu (Jurnal Akuntansi Universitas Muhammadiyah Kupang, 2024)
ABSTRACT The objectives of this study are to determine: 1) The planning of financial management in Uluwae II Village in accordance with village financial management planning as per Ministry of Home Affairs Regulation Number 113 of 2014; 2) The implementation of financial management in Uluwae II Village in accordance with village financial management implementation as per Ministry of Home Affairs Regulation Number 113 of 2014; 3) The administration of financial management in Uluwae II Village in accordance with village financial management administration as per Ministry of Home Affairs Regulation Number 113 of 2014; 4) The reporting of financial management in Uluwae II Village in accordance with village financial management reporting as per Ministry of Home Affairs Regulation Number 113 of 2014; and 5) The accountability of financial management in Uluwae II Village in accordance with village financial management accountability as per Ministry of Home Affairs Regulation Number 113 of 2014. This research is a Descriptive Qualitative study. The sources of data used in this research are Primary and Secondary Data. For Primary Data, the researcher conducted direct interviews to obtain valid data sources, while Secondary Data was taken from documents related to the procedures for implementing Village Financial Management from planning to accountability stages. The subjects of this research are the Head of Uluwae II Village, the Village Secretary and Staff, and the community of Uluwae II Village. Data collection techniques used in this study include Observation, Interviews, and Documentation. The data analysis techniques employed are Data Reduction, Data Display, and Conclusion Drawing (verification). The results of the study indicate that Uluwae II Village has carried out financial management processes in accordance with the provisions stipulated in Ministry of Home Affairs Regulation Number 113 of 2014. Despite some discrepancies and delays in reporting and accountability, overall the village has endeavored to comply with the applicable regulations. Community participation in village development planning demonstrates a commitment to achieving participatory and transparent planning. The village's financial administration is quite good with the assistance of the Village Financial System (SISKEUDES), but there is still a need for improvement in the collection of supporting documents and the preparation of accountability reports. Therefore, improvements are needed in the process of collecting supporting documents and preparing accountability reports to enhance compliance and transparency in village financial management.